(untitled) (Revista Crioula, 2023)
Jorge Amado's Abc de Castro Alves narrates the life of the Bahian poet and builds him as a character, aiming at the exaltation of an engaged Brazilian literature. Thus, we seek to understand how Alves is woven as a literary element, his relationship with Jorge Amado's literary/political project and the idea of sertão as a libertarian field. To this end, the methodology used was qualitative and bibliographic, listing Rossi (2009), Pontes (2017) and Figueiredo (1998). This research is justified by the sharing of the dialog between Jorge Amado and the poetic work of Castro Alves who, although they are subjects of different times, are guided by the ideational construct of freedom.